1991
DOI: 10.1001/jama.266.10.1390
|View full text |Cite
|
Sign up to set email alerts
|

Standardized patient encounters. A method for teaching and evaluation

Abstract: The primary goal of medical education is to foster development of clinical competence in trainees at all levels. Variable clinical experience, inconsistent methods of instruction, and ambiguous evaluation criteria undermine this goal. Standardized patients, trained to consistently portray a wide variety of clinical cases, can help overcome many of these educational problems. This article describes the development and application of standardized patients throughout medical training at The University of Texas Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 26 publications
0
43
0
3
Order By: Relevance
“…[12][13][14] Our curriculum has the distinguishing feature of a longitudinal clinical experience between learners and SPs/daughters over multiple SP sessions representing a single unfolding dementia case. Studies have shown that SPs are at least as effective as faculty in teaching the medical interview to first-year medical students 15 and that SP encounters can be a useful tool in teaching medical students the art of communicating.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Our curriculum has the distinguishing feature of a longitudinal clinical experience between learners and SPs/daughters over multiple SP sessions representing a single unfolding dementia case. Studies have shown that SPs are at least as effective as faculty in teaching the medical interview to first-year medical students 15 and that SP encounters can be a useful tool in teaching medical students the art of communicating.…”
Section: Discussionmentioning
confidence: 99%
“…Costs diminish once a programme is established, and overall may actually prove to be cheaper given the staff time saved in teaching and assessment (Ainsworth et al, 1991;Kelly & Murphy, 2004). Examinees may be justifiably disappointed if the costs of using standardised patients are passed directly to them (Wettach, 2003).…”
Section: Advantages and Disadvantages Of Simulated Patientsmentioning
confidence: 99%
“…Simulated interviews were chosen to increase the emotional level of the interview, to standardize patients' history and reactions and to standardize the interview's characteristics. This was carried out because simulated interviews have become increasingly accepted over their 30-year history as a valid method used to represent how a physician would perform with real patients [30][31][32][33][34][35][36][37]. Simulated interviews, moreover, allow to reduce the possible bias that may derive from a wide range of patients' history and reactions and from a wide range of interview characteristics.…”
Section: Simulated Interviewmentioning
confidence: 99%